Tingkat Kesadaran Hukum Mahasiswa Terhadap Peraturan Kampus - Julpin Carles Waruwu (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
This study aims to determine the level of legal awareness among university students regarding the regulations in the campus environment. Legal awareness is an important aspect in shaping the character of law-abiding and responsible citizens, particularly among students as agents of change. The research method used is descriptive quantitative, with data collection conducted through questionnaires distributed to 100 students from various faculties. The results show that the level of legal awareness among students falls into the moderate category, with most students being aware of the existence of campus regulations, but not fully understanding their content and associated sanctions. Factors influencing legal awareness include the dissemination of regulations, enforcement of discipline by the campus authorities, and the role of lecturers in Citizenship Education (PPKn) learning. These findings highlight the importance of continuous legal education in higher education institutions to foster a strong legal culture.